Muhammadiyah Berkemajuan: Najib Burhani Prespektif - Anzalman, Anzalman; Elhusein, Shofwan Karim; Lahmi, Ahmad; Asmaret, Desi; Dahlan, Dasrizal; Thaheransyah, Thaheransyah (Universitas Pahlawan Tuanku Tambusai, 2024)
Penelitian ini mengeksplorasi konsep